2023
DOI: 10.1002/anie.202304017
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of NO2 on TiO2: Evidence of a New Source of N2O5

Abstract: N2O5 is an important intermediate in the atmospheric nitrogen cycle. Using a flow tube reactor, N2O5 was found to be released from the TiO2 surface during the photocatalytic oxidation of NO2, revealing a previously unreported source of N2O5. The rate of N2O5 release from TiO2 was dependent on the initial NO2 concentration, relative humidity, O2/N2 ratio, and irradiation intensity. Experimental evidence and quantum chemical calculations showed that NO2 can react with the surface hydroxyl groups and the generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…An advantage of this technique is that it does not suffer from high and variable chemical interferences compared with TD-CIMS. In recent years, this method has been widely used to measure N 2 O 5 both in laboratory and field experiments , I + N 2 O 5 normalI ( normalN 2 normalO 5 ) …”
Section: Introductionmentioning
confidence: 99%
“…An advantage of this technique is that it does not suffer from high and variable chemical interferences compared with TD-CIMS. In recent years, this method has been widely used to measure N 2 O 5 both in laboratory and field experiments , I + N 2 O 5 normalI ( normalN 2 normalO 5 ) …”
Section: Introductionmentioning
confidence: 99%
“…7 Chu et al revealed a new pathway for the oxidation of NO 2 to form N 2 O 5 on the TiO 2 surface. 11 In the case of metal ions, there is concern about their impact on human health due to their strong affinity to biological macromolecules. 12 As for source specificity of metal ions, it is often used to determine the origin of particulate pollution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ma et al found that TiO 2 could result in nitrate decomposition to yield higher reactive nitrogen species concentration than SiO 2 . Chu et al revealed a new pathway for the oxidation of NO 2 to form N 2 O 5 on the TiO 2 surface …”
Section: Introductionmentioning
confidence: 99%
“…As an important carrier of nitrogen energy, nitrogen oxide (NO) is predominantly utilized as an alternative precursor for ammonia (NH 3 ) synthesis to avoid dissociating the inert NN bond in N 2 molecules. Since the 1990s, many advanced approaches, by the application of electro-, photo-, and plasmon-driven routes, have been developed to conduct the NO reduction reaction (NORR) for its value-added conversion under ambient conditions. Although the NH 3 synthesis rate from NORR is significantly promoted in recent literature, the key challenge still lies in that the conversion ratio of NO is far below practicability as a result of the ultralow solubility of NO in reaction solutions. Unlike harmless N 2 that is the feedstock for Haber–Bosch NH 3 synthesis, NO is one of the major air pollutants. That is, the limited conversion ratio of the current NORR route would potentially contribute more to the emission of the contaminant than to its upcycling.…”
Section: Introductionmentioning
confidence: 99%